Faktor-Faktor yang Mempengaruhi Pelaporan Keuangan UMKM Berdasarkan SAK EMKM - Maidar Maidar; Fitri Yunina; Natasha Fitria (AKUNTANSI 45, 2024)
The purpose of this study is to determine the simultaneous and partial influence of education level, accounting understanding and business age on financial reporting based on SAK EMKM on MSMEs. The data population in this study amounted to 78 MSMEs spread across Aceh Besar Regency. The sampling method used is by random sampling so that every individual population in Darul Imarah District, Aceh Besar Regency is represented. The data analysis techniques used in this study are descriptive analysis and multiple linear regression with the help of software statistics for the social science (SPSS) version 25.0. The results of the study show that the level of education, operating period and accounting understanding have a significant effect on financial reporting based on SAK EMKM for MSMEs in Darul Imarah District, Aceh Besar Regency simultaneously or partially.